Dietary protein dilution limits dyslipidemia in obesity through FGF21-driven fatty acid clearance - Maida, Adriano; Augustin, Hellmut; Herzig, Stephan; Rose, Adam J. (The journal of nutritional biochemistry, 2018)
Recent studies have demonstrated that dietary protein dilution (PD) can promote metabolic inefficiency and improve glucose metabolism. However, whether PD can promote other aspects of metabolic health, such as improve systemic lipid metabolism, and mechanisms therein remains unknown. Mouse models of obesity, such as high-fat-diet-fed C57Bl/6 N mice, and New Zealand Obese mice were fed normal (i.e., 20%P) and protein-dilute (i.e., 5%EP) diets. FGF21−/− and Cd36−/− and corresponding littermate +/+ controls were also studied to examine gene-diet interactions. Here, we show that chronic PD retards the development of hypertrigylceridemia and fatty liver in obesity and that this relies on the induction of the hepatokine fibroblast growth factor 21 (FGF21). Furthermore, PD greatly enhances systemic lipid homeostasis, the mechanisms by which include FGF21-stimulated, and cluster of differentiation 36 (CD36) mediated, fatty acid clearance by oxidative tissues, such as heart and brown adipose tissue. Taken together, our preclinical studies demonstrate a novel nutritional strategy, as well as highlight a role for FGF21-stimulated systemic lipid metabolism, in combating obesity-related dyslipidemia.
Available online 7 April 2018
Gesehen am 17.09.2019